(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Unlike their Western European and American counterparts, most young Croatian lawyers feel they lack the necessary career support during their studies and later at their workplace. Based on the recent primary data, this study investigates the career development services and experiences, perceived legal education-labour market (mis)match and mentoring insights among final year law students and recent graduates in Croatia. Preliminary findings indicate plenty of room for improvement both in transferring Western good practices and organically creating career support initiatives at the workplace and during legal studies. In addition, this study emphasises the (increased) importance of quality mentoring relations in the circumstances of exogenous shocks such as the global COVID-19 pandemic.